Clinical manifestations of the skin photodamage as a result of a multi-course phototherapy of psoriasis patients - M. B. Zhilova; V. A. Volnukhin; A. S. Dvornikov (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
Goal. To study clinical manifestations and frequency of skin photodamage symptoms in psoriasis patients receiving a longterm multi-course phototherapy. Materials and methods. The study involved 106 patients suffering from psoriasis vulgaris and receiving a multi-course treatment by methods of the PUVA therapy, broadband medium-wave UV therapy and narrowband phototherapy with the wavelength of 311 nm. The average number of courses was 7 while the average number of treatment sessions was 141. Depending on the number of treatment sessions, the patients were divided into three groups: Group 1 (n = 33) - patients that received 50-100 phototherapy sessions, Group 2 (n = 58) - patients that received 101-200 treatment sessions, and Group 3 (n = 15) - patients that received over 200 treatment sessions. The control group comprised 20 psoriasis patients that did not receive any phototherapy before. Major results. The comparative analysis of the entire group of patients receiving a phototherapy revealed a statistically significant incidence of lentigo/sunspots, diffuse skin hyperpigmentation and actinic elastosis vs. the control group. The frequency of clinical manifestations characteristic of the skin photodamage grew as the number of treatment sessions increased. All of the symptoms except for guttate hypomelanosis and venous lakes demonstrated statistically significant dynamics. Conclusion. There is a dose-dependant increase in the frequency of skin photodamage symptoms in patients suffering from psoriasis vulgaris and receiving a long-term multi-course phototherapy.